A Bidirectional Relationship Between Hyperuricemia and Metabolic Dysfunction-Associated Fatty Liver Disease - Yang, Chengzhang; He, Qianjin; Chen, Ze; Qin, Juan-Juan; Lei, Fang; Liu, Ye-Mao; Liu, Weifang; Chen, Ming-Ming; Sun, Tao; Zhu, Qian; Wu, Yonglin; Zhuo, Ming; et al. (Frontiers in Endocrinology, 2022)
Background and aims: Metabolic dysfunction-associated fatty liver disease (MAFLD) is a newly emerged term that is suggested to better reflect the pathogenesis of nonalcoholic fatty liver disease (NAFLD); however, the association between hyperuricemia and MAFLD has not been explored in the Chinese population. Meantime, this study also examined the temporal relationship between the two entities in a longitudinal cohort. Methods: We conducted a retrospective cross-sectional study including 1,587,962 individuals from 19 health check-up centers in China from 2009-2017 and a longitudinal study with 16,112 individuals. A logistic regression model was applied to determine the association between hyperuricemia and MAFLD in a cross-sectional study. The Cox regression model was used to explore the association between hyperuricemia at baseline and subsequent onset of MAFLD or the association between the presence of MAFLD at baseline and the subsequent incidence of hyperuricemia. The cross-lagged analysis was applied to exam the temporal relationship between hyperuricemia and MAFLD. Results: In the cross-sectional study, hyperuricemia showed a strong positive association with MAFLD after controlled potential confounders. In the longitudinal cohorts, hyperuricemia at baseline was associated with the new-onset of MAFLD, with a hazard ratio (HR) of 1.765 (95% CI: 1.512, 2.060). Interestingly, baseline MAFLD was also associated with the subsequent incidence of hyperuricemia, with an HR of 1.245 (95% CI: 1.106, 1.400). The cross-lagged path analysis revealed a bidirectional relationship between hyperuricemia and MAFLD. Conclusions: The results suggested that hyperuricemia and MAFLD form a vicious cycle, resulting in more deterioration of metabolic status.